THE EFFECT OF PROFITABILITY, SOLVENCY, LIQUIDITY AND FIRM SIZE ON STOCK RETURN - ,; ,; ,; , (LUCRUM : Jurnal Bisnis Terapan, 2025)
Changes in stock return can be determined by the financial performance of companies that are projected in the company's financial statements. The purpose of this study was to determine the effect of financial performance that seen from the level of profitability, solvency, liquidity and firm size on stock returns at the industrial sector in Indonesia Stock Exchange This research is a quantitative and researched in the Indonesia Stock Exchange. Samples were selected using purposive sampling and obtained a total sample of 21 samples. The analytical method in this study used the Smart PLS software by performing a comparison of the PLS. From this study, it can be concluded that profitability have significant effeck on stock returns, while solvency, liquidity and firm size have no significant effect on stock returns.